The large volume and three-dimensional shape of the flexor hallucis longus muscle in sprinters and distance runners - Peter, A.; Hegyi, A.; Kóbor, I.; Gyebnár, G.; Kovács, B. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
We investigated the anatomical characteristics of flexor hallucis longus (FHL) in high-level sprinters and distance runners. We recruited 14 sprinters, and 15 distance runners. The lower leg was scanned using magnetic resonance imaging. All scans were segmented then FHL`s 3-D shape was compared between groups using statistical shape modelling. In addition, we quantified muscle volume and mass, largest anatomical cross-sectional area, muscle length. Considering muscle volume, largest anatomical cross-sectional area and muscle length, we found no significant differences between sprinters and distance runners, and the shape of the muscle was also similar between groups. When compared to studies on non-runners and cadavers, runners in this study had larger FHL volume, which may implicate the role of FHL in running.